Diagnostics of the formation of the cognitive-creative component of the conflictological culture of the future engineer in the process of humanitarian training - Hrechanovska О. (Problems of Engineer-Pedagogical Education, 2019)
The development of a professional worker has always been a problem throughout various educational spheres. Finding the best pedagogical systems and innovations requires an increasingly thorough approach with every passing day. While searching for the effectiveness of education an important element is being lost, which is the development of not only a professional, but also the formation of vital and spiritually holistic qualities, especially in technical institutions of higher education, where this function is performed by humanitarian disciplines. During the study of humanitarian disciplines conflictological culture is formed, which is an important component of professional competence.The article proposes substantiation and experimental verification of the formation of the cognitive and creative component of conflictological culture of future technical specialists, and presents the author’s own definition of conflictological culture of future technical specialists. The research is based on the analysis of scientific works regarding the definitions of creativity, cognition, and substantiates the importance of cognitive and creative component within conflictological culture. The essence of humanitarian disciplines in the educational process of technical institutions of higher education and the importance of introducing interactive technologies while studying them are revealed.A pedagogical experiment was conducted to diagnose the level of the cognitive and creative component of students and the functioning of the pedagogical system of the formation of conflictological culture of future technical specialists. In total, 564 people took part in the experiment (EG —286 respondents, Vinnytsia National Technical University and CG —278 respondents, National Forestry University of Ukraine, Lviv). The research was conducted in the process of studying humanitarian disciplines of the cultural cycle and relied on a number of methods that were used, and the results were experimentally verified. These methods included resolving a problem situation (futuristic and surrealistic), doing the test “Defining the social creativity of the individual”, working with the authorial book “Workbook for independent work on the discipline “Pedagogy, Psychology and Teaching Methods in Higher School”” for masters. According to the Kolmogorov-Smirnov criterion value calculations, the results of thelevels of formation of the cognitive and creative component of conflictological culture of future technical specialists, at the level of significance of 95%, demonstrate that the difference between the levels of formation of the cognitive and creative component of conflictological culture of future technical specialists in EG and CG groups is significant, which is in favor of the results of EG group and proves the effectiveness of the proposed pedagogical system for the formation of conflictological culture of future technical professionals.